As origens ideológicas da Estratégia de Segurança Nacional dos Estados Unidos da América de 2002: reflexões nos dez anos do Onze de Setembro (Meridiano 47 - Journal of Global Studies, 2017)
This article attempts to identify the ideological origins of the 2002 National Security Strategy of the United States of America (NSS-2002), which may be traced back to the competition among strategies in the 1990’s foreign policy-making circles. I believe that the NSS-2002, the main channel for the War on Terror, derives from the same ideological thinking of the strategy of primacy.